Development of CE-C4D Method for Determination Tropane Alkaloids - Gołąb, Małgorzata; Przybyłowska, Martyna; Kubáň, Petr; Itterheimová, Petra; Woźniakiewicz, Michał (Molecules (Basel, Switzerland), 2021)
A fast method for the determination of tropane alkaloids, using a portable CE instrument with a capacitively coupled contactless conductivity detector (CE-C4D) was developed and validated for determination of atropine and scopolamine in seeds from Solanaceae family plants. Separation was obtained within 5 min, using an optimized background electrolyte consisting of 0.5 M acetic acid with 0.25% (w/v) β-CD. The limit of detection and quantification was 0.5 µg/mL and 1.5 µg/mL, respectively, for both atropine and scopolamine. The developed method was validated with the following parameters-precision (CV): 1.07-2.08%, accuracy of the assay (recovery, RE): 101.0-102.7% and matrix effect (ME): 92.99-94.23%. Moreover, the optimized CE-C4D method was applied to the analysis of plant extracts and pharmaceuticals, proving its applicability and accuracy.
Keywords: alkaloidy Solanaceí; elektroforéza kapilární; CE-C4D; Limit of Detection; conductivity detection; tropane alkaloids; limita detekce; scopolamine; Scopolamine; atropine; Atropine; capillary electrophoresis; Solanaceous Alkaloids; skopolamin; atropin; Solanaceae; Electrophoresis, Capillary